THE INFLUENCE OF E-COMMERCE, BRAND IMAGE, PRODUCT QUALITY ON PURCHASING DECISIONS FOR PORTO SANDALS AT SHOPEE LASBIO FOOTWEAR - Ihdina Gustina; Dedy Lazuardi; Azrina Amalia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine the effect of E-Commerce, Brand Image, and Product Quality on consumer purchasing decisions at the Lasbio Footwear online store on the Shopee platform. The research method used is quantitative with a survey approach. The research sample consisted of 100 respondents who were Lasbio Footwear consumers. The data analysis technique used is multiple linear regression with the help of SPSS software. The results showed that partially or simultaneously, the variables of E-Commerce, Brand Image, and Product Quality had a positive and significant effect on Purchasing Decisions. Among the three variables, Product Quality has the most dominant influence. The coefficient of determination (R²) value of 0.482 indicates that 48.2% of the variation in Purchasing Decisions can be explained by the three independent variables, while the rest is influenced by other factors not examined. Thus, this study concludes that the success of selling Lasbio Footwear products at Shopee is influenced by the effective use of e-commerce platforms, the strength of brand image, and the quality of products offered to consumers.